Multi-species analysis of inflammatory response elements reveals ancient and lineage-specific contributions of transposable elements to NF-kB binding - Wang, Liangxi; Taylor, Tiegh; Rathnakumar, Kumaragurubaran; Khyzha, Nadiya; Liang, Minggao; Alizada, Azad; Campitelli, Laura F.; Pour, Sara E.; Patel, Zain M.; Antounians, Lina; Tobias, Ian C.; Hou, Huayun; et al. (Genome Research, 2025)
Transposable elements (TEs) provide a source of transcription factor (TF) binding sites that can rewire gene regulatory networks. NF-kB is an evolutionarily conserved TF complex primarily involved in innate immunity and inflammation. The extent to which TEs have contributed to NF-kB responses during mammalian evolution is not well established. Here, we perform a multi-species analysis of TEs bound by the NF-kB subunit RELA in response to the proinflammatory cytokine TNF. By comparing RELA ChIP-seq data from TNF-stimulated primary aortic endothelial cells isolated from human, mouse, and cow, we find that 55 TE subfamilies are associated with RELA-bound regions, many of which reside near TNF-responsive genes. A prominent example of lineage-specific contribution of transposons comes from the bovine SINE subfamilies Bov-tA1/2/3 which collectively contributed over 14,000 RELA-bound regions in cow. By comparing RELA binding data across species, we also find several examples of RELA motif-bearing TEs that colonized the genome prior to the divergence of the three species and contributed to species-specific RELA binding. For example, we find human RELA-bound MER81 instances are enriched for the interferon gamma pathway and demonstrate that one RELA-bound MER81 element can control the TNF-induced expression of interferon gamma receptor 2 (IFNGR2). Using ancestral reconstructions, we find that RELA containing MER81 instances rapidly decayed during early primate evolution (>50 million years ago [MYA]) before stabilizing since the separation of Old World monkeys (<50 MYA). Taken together, our results suggest ancient and lineage-specific transposon subfamilies contributed to mammalian NF-kB regulatory networks.